The Influence of Personal Innovativeness on ChatGPT Continuance Usage Intention among Students - Satrio Tegar Sadewo; Ratnawati, Shinta; Giovanni, Axel; Widayanti, Ipuk (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
The rapid advancement of generative AI technologies, such as ChatGPT, has introduced significant innovations across various sectors. However, the factors influencing the continuance usage intention of these technologies remain underexplored, particularly among university students in Indonesia. This study investigates the role of Personal Innovativeness within the framework of the Technology Acceptance Model (TAM) in determining students' intentions to continue using ChatGPT. The study used a quantitative method, involving a survey of 252 Indonesian university students. The survey measured Personal Innovativeness, Perceived Ease of Use, Perceived Usefulness, and Continuance Usage Intention using validated measures on a Likert scale with five points. Partial Least Squares Structural Equation Modeling (SEM-PLS) was utilized to evaluate the evidence. The results demonstrate that all three factors have a favorable effect on the desire to continue utilizing ChatGPT. Theoretically, this study expands the Technology Acceptance Model (TAM) by incorporating Personal Innovativeness, offering new insights into factors that sustain long-term technology engagement. This integration contributes to the growing body of knowledge on technology adoption and its continued use, especially within educational contexts. Practically, the results underscore the importance of developing user-friendly and beneficial AI tools and fostering an innovative mindset among students to enhance sustained engagement. Future research should consider longitudinal studies and more diverse populations to further elucidate the factors influencing the continuance usage intention of AI technologies in educational contexts. These insights have significant implications for educators and developers aiming to improve the adoption and sustained use of AI tools like ChatGPT in education.